Empirical perspectives of transactive memory systems: a meta-analysis. Issue 7 (11th August 2020) - Zhou, Zikai; Pazos, Pilar
Abstract : Purpose: The purpose of this study is to synthesize the previous empirical studies on transactive memory systems (TMS) through a meta-analytical approach and test the proposed model for the relationships between TMS and different types of team outcomes. Design/methodology/approach: TMS refers to shared memory systems developed among a group of people for encoding, storage and retrieval of their different knowledge domains. They have been widely used in group or organization settings to describe the cumulative knowledge in a group of multi-disciplinary experts. Previous literature suggests TMS as a critical concept for explaining group performance, but few studies were conducted to integrate the literature findings to identify the relationships between TMS and team outcomes. Findings: The findings suggest that TMS is more strongly linked to affective outcomes than behavioral or performance outcomes. In addition, the authors find that the specific operationalization of TMS does not affect the relationship between TMS and team outcomes. There was not enough support for significant effects of group size and research setting on the relationships between TMS and team outcomes, which indicates that both laboratory and field studies have similar potential to generate valuable results for the research of TMS. Originality/value: This study contributes to the body of knowledge on team effectiveness by investigating the links between TMS and team effectiveness through a broad definition of outcomes that include tangible constructs, such as performance, as well as behavioral and affective outcomes. By exploring the relationships through this broad conceptualization of team effectiveness, the authors can better understand the particular effects of TMS on different key aspects used to determine success in teams.